2021
DOI: 10.3390/diagnostics11081504
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Usefulness of 131I-SPECT/CT at Both Radioiodine Ablation and during Long-Term Follow-Up in Patients Thyroidectomized for Differentiated Thyroid Carcinoma: Analysis of Tissue Risk Factors Ascertained at Surgery and Correlated with Metastasis Appearance

Abstract: 131I Single-photon emission computerized tomography/computerized tomography (SPECT/CT) in the management of patients thyroidectomized for differentiated thyroid carcinoma (DTC) was further investigated. Retrospectively, 106 consecutive DTC patients were enrolled at the first radioiodine ablation, 24 at high risk (H), 61 at low risk (L) and 21 at very low risk (VL). 131I whole-body scan (WBS) and SPECT/CT were performed after therapeutic doses using a hybrid dual-head gamma camera. At ablation, SPECT/CT correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…These results are in agreement with the data reported also by other authors who observed that multifocality/multicentricity in their PC/GD series was not associated with disease recurrent/persistence during follow-up nor with a significant increase in the risk of DTC-related mortality [ 14 , 24 ]. However, in other studies on larger case series, multifocality, together with other risk factors, including a few cases with GD, was associated with metastasis appearance in the follow-up of PC patients [ 47 , 51 ].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These results are in agreement with the data reported also by other authors who observed that multifocality/multicentricity in their PC/GD series was not associated with disease recurrent/persistence during follow-up nor with a significant increase in the risk of DTC-related mortality [ 14 , 24 ]. However, in other studies on larger case series, multifocality, together with other risk factors, including a few cases with GD, was associated with metastasis appearance in the follow-up of PC patients [ 47 , 51 ].…”
Section: Discussionmentioning
confidence: 91%
“…Metastases from DTC after thyroidectomy and radioiodine ablation are usually identified using 131 I whole-body scan (WBS) [ 34 , 35 , 36 ] and the more recent SPECT/CT before [ 37 , 38 , 39 , 40 ] and after ablation [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ], as well as during long-term follow-up [ 48 , 49 , 50 , 51 ]. Together with nuclear medicine procedures, radiologic exams and sequential serum thyroglobulin assays were performed.…”
Section: Introductionmentioning
confidence: 99%
“…2A). 10,12,25,26,31,37,38 Meta-analysis of 4 studies, encompassing a total of 230 extracervical lesions, indicated that adding SPECT/CT to WBS resulted in a 20% increase in conclusive readings compared with WBS alone (RR, 1.20; 95% CI, 1.13-1.28; P < 0.00001) (Fig. 2B).…”
Section: Feasibility Of Conclusive Readingmentioning
confidence: 99%
“…A widely used radioisotope, radioiodine, plays a critical role in the diagnosis and treatment of DTC, such as 123 I, 124 I, and 131 I. 131 I SPECT/CT has become a routine tool for visualizing the lesions and evaluating distant metastases in patients receiving radioactive iodine therapy ( 29 ). 124 I PET/CT could improve the sensitivity and spatial resolution of SPECT/CT, leading to superior diagnostic performance of post-therapy 131I-WBS.…”
Section: Molecular Imaging In Detection Of Dedifferentiated Thyroid C...mentioning
confidence: 99%